STUDI KASUS PERSONAL BRANDING KONTEN KREATOR PADA AKUN TWITTER @BROJABROOO - Dhanar Jabro Febiansah; Sudono Syueb; Siska Armawati Sufa; Eny Ratnasari (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2020)
Personal branding for a content creator is needed so that there are characteristics that are remembered by followers. The development of information technology also encourages the emergence of various social media that can be used as a means of forming personal content branding creators. This study aims to analyze the personal branding carried out by creator content in the social media account Twitter @brojabrooo. This research will try to illustrate clearly the process of managing personal branding in the @brojabrooo account using the case study method.As a content creator, Jabro has done personal branding to distinguish himself from other creator content. Researchers found 8 main concepts in building personal branding in accordance with what was stated by Peter Montoya (2002). Jabro built personal branding as a content creator via Twitter and fulfilled the 8 main concepts. This can be seen from Jabro's tweet that contains a variety of content, mostly dominated by photos and videos about him. Personal branding built by Jabro is a content creator who wants to entertain netizens and consistently use East Javanese.